Strategies for managing fungicide resistance in the Brazilian tropical agroecosystem: Safeguarding food safety, health, and the environmental quality - Ceresini, Paulo Cezar [UNESP]; Silva, Tatiane Carla [UNESP]; Vicentini, Samara Nunes Campos [UNESP]; Júnior, Rui Pereira Leite; Moreira, Silvino Intra [UNESP]; Castro-Ríos, Katherin [UNESP]; Garcés-Fiallos, Felipe Rafael [UNESP]; Krug, Loane Dantas [UNESP]; de Moura, Suzany Santos [UNESP]; da Silva, Abimael Gomes [UNESP]; de Paiva Custódio, Adriano Augusto; May De Mio, Louise Larissa; et al. (Springer Nature, 2024)
Fungicide resistance is an alarming challenge for the Brazilian tropical agricultural systems, with major implications for food safety, human and animal health, as well as for the environment. This review explores strategies to address fungicide resistance within the Brazilian agroecosystem context. We examined historical and current scenarios of fungicide resistance in the Brazilian agroecosystems and the approaches to delay the emergence and mitigate the selection of resistant variants. Our review indicates that the prevalence of resistance in field populations of key plant pathogens in Brazil was due to failures in the implementation of preventive measures. To address this issue, alternative evolutionary-smart strategies against fungicide resistance are proposed, emphasizing institutional actions and public policies. Crucial steps involve strengthening national networks for large-scale foliar and seed fungicide efficacy testing and resistance monitoring, as well as imposing tighter restrictions on the labeling of high-risk single-active formulations. Additionally, the integration of non-chemical disease management strategies and the establishment of a centralized database and information system on fungicide resistance in Brazil are identified as essential for effective resistance monitoring and informed decision-making. To enhance fungicide resistance management, the adoption of a warning system (e.g., based on aerobiology- or on weather-monitoring) for predicting disease epidemics and minimizing fungicide applications is recommended. Increased funding, collaboration, mandatory reporting, and capacity building are required to overcome these challenges. In addition, promoting integrated disease management approaches is vital. By implementing these tailored strategies, Brazil can actively contribute to safeguarding its food safety, protecting human and animal health, and preserving the delicate balance of its unique agroecosystem. The adoption of evolutionary-smart strategies against fungicide resistance will prolong fungicide efficacy, reduce economic costs, and minimize environmental impacts, ensuring sustainable and resilient agriculture in Brazil.
Keywords: Aerobiology-based inoculum monitoring tools; Centralized database on fungicide resistance; Evolutionary-smart anti-resistance strategies; Information system; Mycosphaerellaspp; Phakopsora pachyrhizi; Pyricularia oryzae; Sustainable and resilient agriculture